The Berliner Philharmoniker at the Lucerne Festival moving to modern times - Britten, Benjamin 1913-1976; Bruckner, Anton 1824-1896 (Accentus Music, 2011)
"Night" was the motto of the Lucerne Summer Festival 2011. Accordingly, the Berliner Philharmoniker, under Sir Simon Rattle's direction, explored in their Lucerne series Moving to Modern Times the phenomenon of the night by pairing up in an outstanding concert the late romantic Anton Bruckner with England's greatest modern composer, Benjamin Britten. While Bruckner's 9th Symphony involves an inner journey, Britten's Nocturne extends into a trance-like meditation on dreaming, the latter presented by acclaimed tenor Ian Bostridge, whose "particular gift for lighting texts from within, and projecting so immediately their images, comes into its own arrestingly in the Nocturne", stated the Gramophone Magazine
Keywords: Songs (High voice) with chamber orchestra; Symphonies; Internet videos